2017
DOI: 10.1155/2017/1391298
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Oxide Nanoparticles Reinforced Electrospun Alginate-Based Nanofibrous Scaffolds with Improved Physical Properties

Abstract: Mechanically robust alginate-based nanofibrous scaffolds were successfully fabricated by electrospinning method to mimic the natural extracellular matrix structure which benefits development and regeneration of tissues. Alginate-based nanofibres were electrospun from an alginate/poly(vinyl alcohol) (PVA) polyelectrolyte complex. SEM images revealed the spinnability of the complex composite nanofibrous scaffolds, showing randomly oriented, ultrafine, and virtually defects-free alginate-based/MgO nanofibrous sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 38 publications
(52 reference statements)
0
32
0
Order By: Relevance
“…Silva et al fabricated scaffold based on alginate reinforced with MgO using electrospinning technique utilized for tissue engineering applications. It was observed that the remaining residue percentage of the alginate‐reinforced MgO membrane was found to higher than the pure alginate scaffolds concluding some residues with MgO were left behind . In our fabricated PU/NiO membrane, the remaining residue was found to higher than the pristine PU which might be the residues of the NiO.…”
Section: Resultsmentioning
confidence: 68%
“…Silva et al fabricated scaffold based on alginate reinforced with MgO using electrospinning technique utilized for tissue engineering applications. It was observed that the remaining residue percentage of the alginate‐reinforced MgO membrane was found to higher than the pure alginate scaffolds concluding some residues with MgO were left behind . In our fabricated PU/NiO membrane, the remaining residue was found to higher than the pristine PU which might be the residues of the NiO.…”
Section: Resultsmentioning
confidence: 68%
“…Further at 1,000°C, the electrospun PU/titanium dioxide nanocomposites exhibited high residual weight percentage of 11.83%, while the electrospun PU nanofibers exhibited weight percentage of only 0.47% which indicating presence of titanium dioxide in the PU. Silva et al prepared electrospun scaffold based on alginate reinforced with magnesium oxide (MgO) for tissue engineering applications. It was observed that the alginate reinforced MgO membrane showed enhanced residue percentage than the pure alginate scaffolds suggesting some residues containing MgO were left behind.…”
Section: Resultsmentioning
confidence: 98%
“…The fabrication of multifunctional nanofibrous materials that have different chemical, physical, and mechanical properties by incorporating other components offers the opportunity to develop advanced products for medical applications [49,52]. Due to its low cost, low toxicity, biocompatibility, and biodegradability, alginate has been extensively studied for biomedical application [58,62,68].…”
Section: Biomedical Applicationsmentioning
confidence: 99%